العوامل المؤثرة على قرارات المستثمرين الأفراد في اقتناء أسهم البنوك الإسلامية الكويتية: دراسة وصفية تحليلية - مرى، صالح راشد (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2016)
This study aims to determine the elements that influence the decisions of individual investors in the shares of Kuwaiti Islamic banks and to reveal the extent to which disclosure in financial reports influences the decisions of these individual investors while also revealing the extent to which the performance of the Kuwait Stock Exchange influences their decisions. The importance of this study manifests in providing solutions to attract the savings of individuals by determining the factors that influence their decisions towards investing in the shares of Kuwaiti Islamic banks. This study was applied to a chosen sample of 320 individual investors who invest in the shares of Kuwaiti Islamic banks in Kuwait. To achieve the research objectives, an instrument was used to study and analyse the factors that influence the individual investors after verifying the instrument's coefficient of reliability and consistency. After applying the instrument to the study sample and analysing the feedback, the study concludes that the awareness of individual investors in the shares of Islamic banks was weak, and that they were uninformed about disclosure in financial reports. The current study concludes with several recommendations, the most important of which are removing all obstacles that prevent individual investors from being aware of the importance of reading and understanding the financial reports of Islamic banks listed in the Kuwait Stock Exchange, and directing the administrations of Islamic banks towards expanding their disclosure and revealing all information that would serve the investors in their investment decisions.